2018
DOI: 10.3892/br.2018.1153
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin improves obesity and insulin resistance in a diabetic patient with Cushing's disease undergoing postoperative steroid therapy: A case report

Abstract: for screening of secondary diabetes mellitus and obesity. Laboratory tests and imaging studies were consistent with Cushing's disease (CD). The patient underwent transsphenoidal pituitary surgery. The patient exhibited loss of body weight (85.9 to 80.0 kg), improved glycated hemoglobin (HbA1c) (11.2 to 7.8%) and required lower doses of insulin (112 to 46 U/day) 6 months after surgery. The patient's body weight and daily insulin dose remained stable during the following 5 months (6-11 months after surgery). At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[ 21 ] Moreover, canagliflozin was found to improve obesity and insulin resistance in a diabetic patient with Cushing disease undergoing postoperative steroid therapy. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] Moreover, canagliflozin was found to improve obesity and insulin resistance in a diabetic patient with Cushing disease undergoing postoperative steroid therapy. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…A case study has been shown that ACTH and cortisol levels were inadequately increased in patients with T2DM [21] . Moreover, canagliflozin was found to improve obesity and insulin resistance in a diabetic patient with Cushing disease undergoing postoperative steroid therapy [22] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation